PLGA/Additive thin film formulation using the ultrasonic stent sprayer - Ang, Ren Jie (2011)
In recent years, Drug Eluting Balloons (DEB) has been gaining attention and popularity in research over Drug Eluting Stents (DES) due to its many advantages over the DES system. Though clinical trials had shown that DES had been successfully in implantation and lowering the risk of restenosis, another problem associated with it was the onset of late stent thrombosis. However, DEB does not have such problems and has certain advantages over the DES as listed below. 1) Allowing for homogenous drug transfer to the vessels walls, 2) Rapid release of high concentration of drugs, 3) Reduction of the onset of late stent thrombosis, 4) Adopted in areas whereby stents are not used or desirable, 5) Overdependence on antiplatelet therapy of DES patients With all these advantages in mind, DEB is growing to be a viable competitor for the DES. Therefore, there is a need for more research and development of the DEB in order to compete with the DES as the next medical device for the future. There are many ways to coat a thin film on a DEB and the focus of this project would be the usage of the Sono Tek Stent Sprayer to spray coat a thin homogenous layer of polymer with a thickness in the range of 10 um to 20um. By varying the 5 process parameters such as the concentration of polymer, flow rate, rotation rate, transverse rate and number of loops, different thickness and morphology of films could be produced by the usage of the Sono Tek Stent Sprayer. In this project, smooth polymer films that have thickness in the range of 10um to 20 um was fabricated by the Sono Tek Stent Sprayer, making it a viable mean of spray coating for high quality polymer thin films.